(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Together with a heterogeneous student society caused by the expansion of higher education and the multitudinous attendance the phenomenon of attrition has also emerged. There are many definitions of dropping out; therefore, those who leave higher education without any qualifications are considered dropouts in our study. According to the literature, there are many reasons behind the dropout such as the lack of appropriate learning methods, skills and financial resources and the inadequate integration in higher education, etc. In our paper, the possible dropout risk factors, which can occur before enrolling higher education, are being identified and analysed. The national data of the 2017 and 2018 admissions databases were used during the examination. The results show that several dropout risk factors can be detected in the admission applications, and as a Hungarian characteristic, the most significant of them all is the lack of a language certificate.